Phase Equilibria of Sub-Neptunes and Super-Earths - Edward D. Young; Lars Stixrude; James G. Rogers; Hilke E. Schlichting; Sarah P. Marcum (The Planetary Science Journal)
We investigate the consequences of nonideal chemical interaction between silicate and overlying hydrogen-rich envelopes for rocky planets using basic tenets of phase equilibria. Based on our current understanding of the temperature and pressure conditions for complete miscibility of silicate and hydrogen, we find that the silicate-hydrogen binary solvus will dictate the nature of atmospheres and internal layering in rocky planets that garnered H _2 -rich primary atmospheres. The temperatures at the surfaces of supercritical magma oceans will correspond to the silicate-hydrogen solvus. As a result, the radial positions of supercritical magma ocean–atmosphere interfaces, rather than their temperatures and pressures, should reflect the thermal states of these planets. The conditions prescribed by the solvus influence the structure of the atmosphere, and thus the transit radii of sub-Neptunes. Separation of iron-rich metal to form metal cores in sub-Neptunes and super-Earths is not assured due to prospects for neutral buoyancy of metal in silicate melt induced by dissolution of H, Si, and O in the metal at high temperatures.